A novel xylan degrading β-D-xylosidase: purification and biochemical characterization - Michelin, Michele (2012)
Aspergillus ochraceus, a thermotolerant fungus isolated in Brazil from decomposing materials, produced an extracellular b-xylosidase that was purified using DEAE-cellulose ion exchange chromatography, Sephadex G-100 and Biogel P-60 gel filtration. b-xylosidase is a glycoprotein (39 % carbohydrate content) and has a molecular mass of 137 kDa by SDS-PAGE, with optimal temperature and pH at 70 C and 3.0–5.5, respectively.b-xylosidase was stable in acidic pH (3.0–6.0) and 70 C for 1 h. The enzyme was activated by 5 mM MnCl2 (28 %)and MgCl2 (20 %) salts. The b-xylosidase produced by A. ochraceus preferentially hydrolyzed p-nitrophenyl-b- D-xylopyranoside, exhibiting apparent Km and Vmax values of 0.66 mM and 39 U (mg protein)-1 respectively, and to a lesser extent p-nitrophenyl-b-D-glucopyranoside. The enzyme was able to hydrolyze xylan from different sources,suggesting a novel b-D-xylosidase that degrades xylan. HPLC analysis revealed xylans of different compositions which allowed explaining the differences in specificity observed by b-xylosidase. TLC confirmed the capacity.